Commercial Informatian Services: A Business Untapped in India - Shah, P.C. (DESIDOC Journal of Library & Information Technology, 2002)
The developments in information technology and the economic scenario all over the world pose challenge to the present set up of library culture. The private sector has already invaded the peripheral areas of library activities and poses a serious threat to libraries, The author discusses the users behavior and need for information in the present context and the factors affecting optimal utilisation of libraries. The advantages of a private commercial library and the problems it may face in future are also mentioned. http://dx.doi.org/10.14429/dbit.15.5.3195